8.5/8.6-mm Excimer Laser–Assisted Penetrating Keratoplasties in a Tertiary Corneal Subspecialty Referral Center: Indications and Outcomes in 107 Eyes. Issue 7 (July 2020) - Alfaro Rangel, Raul; Szentmáry, Nóra; Lepper, Sabine; Daas, Loay; Langenbucher, Achim; Seitz, Berthold
Abstract : Purpose: To report the indications and outcomes of 8.5/8.6-mm excimer laser–assisted penetrating keratoplasties (PKPs) at a tertiary corneal subspecialty referral center. Methods: This retrospective, descriptive, observational study included 107 PKPs performed in 96 patients (mean age, 53 ± 12 years). The patients' indications for surgery, best-corrected visual acuity, surface regularity index, surface asymmetry index, topographic astigmatism, central endothelial cell density, central corneal thickness, and graft status were recorded preoperatively, 6 weeks postoperatively, and before (12 ± 2 months) and after (19 ± 4 months) the suture removal. Results: The surgeries included 48 primary PKPs and 59 repeat PKPs. The main indications were corneal ectatic disorders (50%), severe corneal keratitis (21%), and corneal scars (16%) in the primary PKP group and highly irregular astigmatism after PKP (51%) and previous graft decompensation (37%) in the repeat PKP group. From preoperative measurements to the last follow-up visit without sutures, we found significant improvements ( P < 0.001 for all) in visual acuity (0.7 ± 0.3 LogMAR to 0.3 ± 0.2 LogMAR), surface regularity index (1.5–1.0), and surface asymmetry index (2.59–1.1). At the last follow-up, the mean outcome measurements did not significantly differ between the primary and repeat PKP groups. Overall, 89 grafts (83%) remained clear at the last follow-up. Conclusions: In cases of ectatic disorders and highly irregular astigmatism after keratoplasty, 8.5/8.6-mm excimer laser–assisted PKP seems to be an excellent treatment option, achieving a significant improvement in visual acuity.